A Compact Reconfigurable Dual Band-Notched Ultra-Wideband Antenna using Varactor Diodes - Sam Weng Yik; Zahriladha Zakaria; Herwansyah Lago; Noor Azwan Shairi (Universitas Ahmad Dahlan, 2018)
In this paper, a reconfigurable dual band-notched ultra-wideband (UWB) antenna is presented. The antenna design consists of a circular shape with two pairs of the L-resonator. To realize the notch characteristics in WLAN at 5.2 GHz and 5.8 GHz bands, the half wavelength of the L-resonator is introduced in the design. The T-shaped notch is etched in the ground to enhance the bandwidth which covers the UWB operating frequency range from 3.219 – 10.863 GHz. The proposed reconfigurable dual band-notched UWB antenna shows good impedance matching for the simulated in the physical layout. Furthermore, the proposed antenna has a compact size of 37.6 x 28 mm2. This proposed reconfigurable design can provide an alternative solution for the wireless system in the designing of a band-notched antenna with a good tuning capability.